On the relation between (verbal and kinesic) downtoning and illocution type - Schoonjans, Steven (Yearbook of the Poznan Linguistic Meeting, 2017)
“Downtoning” can be understood as the nuancing of an utterance in view of the interlocutor’s reaction. Typical downtoners in German include the so-called modal particles, although downtoning can also be expressed in other ways, including at the non-verbal level by means of gestures. Given their meanings, downtoning elements are typically restricted to particular illocution types. The goal of this paper is to investigate how this link between downtoning and illocution type is reflected in the use of these downtoners. This is done for both verbal and gestural downtoners in German and for downtoning patterns in German Sign Language (DGS). The question is addressed from two points of view, looking first at the topology of the downtoners in German and DGS, then at the kind of gestural markers co-occurring with verbal downtoners in German.